An Inclusive Leadership Model Insights From the Tech Industry. Issue 4 (November 2022) - Booker, Dante L.; Williams, Michael R.
Problem: Inclusive leadership models have been introduced to represent a shift from traditional leadership approaches. However, missing from these models are principles of social justice and forward-thinking outcomes for building human relations. An examination of the detrimental consequences of exclusion is needed to realize the benefits of inclusion. Solution: The Deconstructing Exclusion for Inclusive Leadership model, a framework for practice, is offered as a practical guide for deconstructing exclusionary practices and building positive, healthy human relations. The model is supported by affective behaviors and traits and cognitive competencies that inclusive leaders need to discourage exclusion and advocate for more inclusive relationships and social justice outcomes. Stakeholders: Leaders, managers, practitioners, human resource development scholars, researchers, and educators.